2022
DOI: 10.1002/lary.30028
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and the Otolaryngology Residency Match: Rising Incidence of Home Matches

Abstract: Objectives/Hypothesis To quantify the effect of the coronavirus disease 2019 (COVID‐19) pandemic upon the 2020 to 2021 residency match for Otolaryngology‐Head and Neck Surgery (OHNS). Study Design Retrospective cohort design. Methods Residency match outcomes for all applicants to our institution during 2020 to 2021 were collected from the National Residency Matching Program including medical school of origin and matched program. Matches were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…Regardless of region, an overall increase was observed as well during the study period from 19% HP matched applicants on average between 2016-2020 to 29% HP matched applicants in 2021. Two recent studies also identified an increase in applicants matching at their respective home programs [ 6 , 12 ]. Additionally, this was also similar to what was seen in the integrated plastic surgery match, another competitive surgical specialty, in 2021 where there was a 9% increase in HP matches [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of region, an overall increase was observed as well during the study period from 19% HP matched applicants on average between 2016-2020 to 29% HP matched applicants in 2021. Two recent studies also identified an increase in applicants matching at their respective home programs [ 6 , 12 ]. Additionally, this was also similar to what was seen in the integrated plastic surgery match, another competitive surgical specialty, in 2021 where there was a 9% increase in HP matches [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their team attributed the observed difference to a lack of in-person opportunities outside of the applicant’s home program. Bernstein et al 18 investigated geographic trends and home program match trends of otolaryngology during the COVID-19 pandemic and identified a statistically significant increase from the 2020 match to the 2021 match (22% in 2020 to 30% in their COVID-impacted group). Their study did not identify any geographic differences in matching between the cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…There is also only 1 year of information available for COVID-impacted data. In addition, there is a paucity of information regarding the impact of virtual interviewing on the orthopaedic surgery match process during 2020 to 2021 10 , 11 , 18 , 19 . Even if such data existed, the extreme variability in the structure of each virtual rotation would require further analysis based on offerings of the rotation.…”
Section: Discussionmentioning
confidence: 99%
“…With the increased competitiveness of otolaryngology residency programs along with multiple changes to the application process during the time of the COVID-19 pandemic, it is important to determine their impact on applications and residency programs. Previous studies of otolaryngology applicants have used the National Residency Match Program data to show a significant increase in the number of applicants matching at or close to home during the years of the COVID-19 pandemic, likely due to the limitations of away rotations and in-person interviews [ 11 - 12 ]. Studies were performed with dermatology and orthopedics applicants looking more specifically at the change in costs related to the COVID-19 pandemic [ 9 , 13 ].…”
Section: Discussionmentioning
confidence: 99%